BIOEQUIVALENCE STUDY OF GENERIC SALBUTAMOL TABLETS WITH LOGO AND BRANDED GENERIC - Rahmawati, Dewi; Rohmah, Atina Wahdatar; Meliana A J, Marthy; Ambari, Yani; Ningsih, Arista Wahyu; Aristia, Bella Fevi; Klau, Ivan Charles Seran (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Salbutamol is a medication that stimulates beta receptors, particularly beta agonists, which are widely used as a remedy for sudden asthma attacks and those triggered by physical exercise due to its potent and rapid bronchodilating properties. These medications are known as short-acting beta-agonists (SABA). The purpose of this study was to examine in detail the significant differences in dissolution and absorption rates associated with the active ingredient in two pharmaceutically equivalent drug products, and to compare them to determine their bioequivalence. The research methodology involved experimental studies using a quantitative approach, including tests of physical quality, content determination, and dissolution testing. The results of the physical quality test for the uniformity of salbutamol tablet sizes showed that generic branded tablets, brand A, brand C, and brand D had a thickness of 0.10 cm ± 0 and a diameter of 0.50 cm ± 0, brand B had a thickness of 0.20 cm ± 0 and a diameter of 0.60 cm ± 0, and brand E had a thickness of 0.10 cm ± 0 and a diameter of 0.40 cm ± 0. The weight uniformity test results indicated that none of the generic branded tablets, brand B, or brand D deviated from columns A (7.5%) and B (15%), whereas none of the tablets from brands A, C, or E deviated from columns A (10%) and B (20%) ...